Caracterización de los problemas ambientales y su impacto en el desarrollo turístico del cantón Ventanas año 2021 - Muñoz Vera, Deidry Ariana (2022)
This thesis aims to "Characterize the environmental problems and their impact on the tourist development of the Ventanas canton, province of Los Rios, Ecuador". The project is divided into two chapters that describe its development. To begin with, a brief introduction was made, the respective theoretical support which covers general and conceptualized data necessary to then start the execution of the same based on what was investigated. Afterwards, the strategic planning that encompasses the nature of the project was executed, based on a general objective and two specific ones in which I write it below, these are as a general objective Characterize the environmental problems and their impact on the tourist development of the Ventanas canton year 2021 For the collection of information, the survey technique was used, this allowed me to obtain information on the topic or problem raised. Finally, the project determines or makes known in detail some of these problems showing how they can affect the tourist development of the Ventanas canton.